Compllete handyman do-it-yourself encyclopedia : a complilation of special interest projects and manual for the repair and care of homes, autos, appliances, hobby equiipment. VI electricrenge-fireplace (H.S. Stuttman Co, 1975)
931-1.084 p.; 25 cm.